SISTEM BAGI HASIL PADA USAHATANI KARET DI KECAMATAN BATIN XXIV KABUPATEN BATANGHARI PROVINSI JAMBI - Lestari, Puji; Kernalis, Emy; Saputra, Ardhiyan (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This research aims to find out the general description of profit sharing system, calculate the amount of income and to analyze income difference farmers penyakap pattern 1 and pattern II system for rubber farming results in Batin XXIV District Batanghari Regency in Jambi provice. This research was conducted on December 20, 2017 until January 18, 2018 in Jelutih and Durian Luncuk Village. Data analysis method used in this research is quantitative descriptive analysis, that is income analysis of rubber farming system, to analyze difference income of farmer pattern I and pattern II using t test analysis. The result of the research shows that are two pattern of system implementation for the pattern of rubber farming I (35%: 65%) and pattern II (50%: 50%). The income of the biggest penyakap farmers from the implementation of this profit sharing system is found in pattern I, which is Rp. 12,949,498,26 every year. The results of the analysis of different test t showed that are significant differences between penyakap farmers pattern I and pattern II . Keywords: Rubber Farming, Profit Sharing, Income